User-centered design of a personal-use exoskeleton: a clinical investigation on the feasibility and usability of the ABLE Exoskeleton device for individuals with spinal cord injury to perform skills for home and community environments - Nadorf, Franziska; Wright, Mark Andrew; López-Matas, Helena; Porras, Erika; Carnicero-Carmona, Alfons; Hensel, Cornelia; Franz, Steffen; Weidner, Norbert; Vidal, Joan; Opisso, Eloy; Rupp, Rüdiger (Frontiers in Neuroscience, 2024)
IntroductionThe ABLE Exoskeleton has been tested to be safe and feasible for persons with spinal cord injury (SCI) to complete basic skills in clinical settings but has not been tested for use in home and community environments. A user-centered design process was employed to test the feasibility of the current ABLE Exoskeleton (designed for clinical use) for persons with SCI to perform the basic and advanced skills required for home and community environments, to gain crucial feedback for the development of a novel personal-use exoskeleton.MethodsIn this prospective pretest-posttest quasi-experimental study across two SCI centers (Germany, Spain), in-and outpatients with SCI were included into a 22-session training and assessment protocol, utilizing the ABLE Exoskeleton. Feasibility and usability measures [level of assistance (LoA) for basic and advanced skills, donning/doffing-time and LoA] were recorded together with safety outcomes, and participant and therapist satisfaction with the device.Results10 participants (44.4 ± 24 years), with SCI from C5 to T11, (American Spinal Injury Association Impairment Scale A–D) completed the study. In 209 sessions, six device-related adverse events (pain and skin lesions) were reported. Average total time for don and doff was 10:23 ± 3:30 min. Eight participants were able to complete don and doff with minimal assistance or less. Independence to carry out all skills in the device increased significantly for all participants (p < 0.05). Participants with chronic SCI required a significantly (p < 0.05) lower LoA for six of the nine advanced skills than those in the sub-acute phase.DiscussionThis study shows that the ABLE Exoskeleton is safe, feasible and usable for people with SCI in respect to independent donning, doffing and performance of basic and advanced exoskeleton skills. The supervised exoskeleton use in the clinical environment was a highly valuable approach for identifying the challenging tasks and the necessary technological developments that need to be carried out for a personal-use exoskeleton, including a more independent sit-to-stand transition, faster speed of transitions between states and a richer display on the remote control for the user.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT05643313.